2021
DOI: 10.1026/0049-8637/a000235
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Peer Exclusion as Predictor of Students’ Help-Seeking Strategies in Higher Education

Abstract: Abstract. Feeling excluded by fellow students may be associated with lower levels of adaptive help-seeking. In a cross-sectional study, we compared self-reported help-seeking strategies (autonomy-oriented, dependency-oriented, help-seeking avoidance) among N = 418 students in 25 seminar and tutorial groups in the undergraduate introductory courses of two subject domains: computer science and education. Analyses showed that, overall, students reported lower autonomy-oriented help-seeking and higher help-seeking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Payakachat et al [ 50 ] and Finney et al [ 51 ] are more focused on College students’ behavior in seeking academic assistance. In Germany, to better understand self-reported help-seeking strategies, Zander and Hoehne [ 52 ] analyzed autonomy-oriented, dependency-oriented, and help-seeking avoidance in undergraduate computing and pedagogy programs. Schlusche et al [ 53 ] used a survey to investigate the impact of social resources on the relationship between AHS behavior and the academic performance of college students in the lower division.…”
Section: Resultsmentioning
confidence: 99%
“…Payakachat et al [ 50 ] and Finney et al [ 51 ] are more focused on College students’ behavior in seeking academic assistance. In Germany, to better understand self-reported help-seeking strategies, Zander and Hoehne [ 52 ] analyzed autonomy-oriented, dependency-oriented, and help-seeking avoidance in undergraduate computing and pedagogy programs. Schlusche et al [ 53 ] used a survey to investigate the impact of social resources on the relationship between AHS behavior and the academic performance of college students in the lower division.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to computer science students' coping resources in the higher education context, we found that they reported less academic self-efficacy and academic online self-efficacy, as well as more perceived exclusion from the exchanges of their fellow students and uncertainty about belonging to their study program in the second pandemic semester as compared to the first, providing further evidence for the increasing weight of the pandemic. While the latter finding was less surprising given the lack of social interactions with fellow students due to the prolonged contact restrictions, which had been reported as a major pandemic-related stressor in previous studies (Cao et al, 2020;Son et al, 2020;, the generally "chilly" academic exchange and interaction climate among students in the domain of computer science (Garvin-Doxas and Barker, 2004;Zander and Höhne, 2021a), and the results by Elmer et al (2020), who found a decrease in STEM students' nominations in both social interaction and co-studying networks after the onset of the pandemic, the decrease in students' selfefficacy beliefs was somewhat unexpected. Although university students worldwide had reported academic-related changes (e.g., precipitous shift to and maintenance of online classes, difficulty learning online) as a significant stressor during the pandemic (Cao et al, 2020;Son et al, 2020;Clabaugh et al, 2021;Matos Fialho et al, 2021), especially our finding that the students in our sample reported less confidence in their ability to successfully handle academic challenges in digital learning environments over the course of the pandemic was not expected given the supposedly good preparedness of computer science students for the transition to online learning in terms of their digital literacy and frequent interactions in digital environments.…”
Section: The Increasing Weight Of the Pandemic: Higher Perceived Stre...mentioning
confidence: 87%
“…Further, no previous studies have focused on computer science students -a population that is of particular interest because they presumably had more resources to cope with the rapid transition to online teaching, but presumably fewer resources in terms of social support within their academic peer group to cope with the extensive contact restrictions during the pandemic (cf. Garvin-Doxas and Barker, 2004;Zander and Höhne, 2021a). The present study aimed to help fill this gap in the literature by examining computer science students' perceived stress as well as individual psychological and social resources in the higher education context over the course of the COVID-19 pandemic.…”
Section: The Present Studymentioning
confidence: 98%
See 2 more Smart Citations